Designing English Course to Pass STAN Examination - sayuthi (INFOKUM, 2021)
The research aimed to define how important English was learnt for students due to the examination and how to design the material course so that the students had capabilities to pass the English exam of PMB STAN. The research was conducted based on students’ ability who were there in SPC course in Medan. The students were given thirty meetings consisting of subjects which were dealt with the questions of the test. As the result, the subject was derived from the easy one to the difficult one and they were connected each other.